2017
DOI: 10.2147/cia.s138535
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia in the elderly: challenges and solutions

Abstract: Decreased serum sodium concentration is a rather frequent electrolyte disorder in the elderly population because of the presence of factors contributing to increased antidiuretic hormone, the frequent prescription of drugs associated with hyponatremia and also because of other mechanisms such as the “tea and toast” syndrome. The aim of this review is to present certain challenges in the evaluation and treatment of hyponatremia in the elderly population and provide practical solutions. Hyponatremia in elderly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
1
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(148 citation statements)
references
References 96 publications
4
111
1
14
Order By: Relevance
“…Similarly, with other biomarkers of hydration status such as blood sodium (normal values 135-142 mEq/L), only 27% of the analyses showed adequate sodium levels; 40% with a diagnosis of hypernatremia and 33% with hyponatremia. Both situations, hyponatremia and hypernatremia, in addition to increasing health risk, are indicators of hydro-electrolyte imbalance in this population group [14]. Other biomarkers of hydration status, such as haematocrit showed normal values in most of the population (95% CI values between 39.3 and 41.0).…”
Section: Volunteer's Nutritional and Hydration Biomarkers Characterismentioning
confidence: 85%
“…Similarly, with other biomarkers of hydration status such as blood sodium (normal values 135-142 mEq/L), only 27% of the analyses showed adequate sodium levels; 40% with a diagnosis of hypernatremia and 33% with hyponatremia. Both situations, hyponatremia and hypernatremia, in addition to increasing health risk, are indicators of hydro-electrolyte imbalance in this population group [14]. Other biomarkers of hydration status, such as haematocrit showed normal values in most of the population (95% CI values between 39.3 and 41.0).…”
Section: Volunteer's Nutritional and Hydration Biomarkers Characterismentioning
confidence: 85%
“…Symptoms typically associated with hyponatremia (including somnolence, headache, nausea, vomiting, convulsion, and partial seizures with secondary generalization) were reported more frequently in patients with the lowest minimum postdose [Na + ] levels (Group A) than in patients with no postdose [Na + ] measurements below 135 mEq/L (Group D) in the adjunctive trials. Similarly, dizziness, nausea, blurred vision, and diplopia were more frequent in patients with a moderate reduction in minimum postdose [Na + ] level (Group B) compared with Group D. In the monotherapy trials, dizziness, nausea, vomiting, fatigue, blurred vision, and nasopharyngitis were more frequent in Group A than in in Group D, and dizziness and nasopharyngitis were more frequent in patients in Group B vs Group D. Overall, somnolence, headache, nausea, and vomiting, all of which can be symptoms of acute hyponatremia, 26 were generally more frequent in patients with low [Na + ] in these trials of ESL, suggesting that [Na + ] ≤125 mEq/L, and even ≤130 mEq/L, may sometimes be symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…The body is more prone to have hyponatremia with increasing age and therefore it is commonly seen in the elderly population [2,3,7,9,11,12]. Elderly population often have co-morbid conditions like multiple endocrinopathies, hypothyroidism, heart failure, chronic kidney disease, liver failure, hypertension, diabetes mellitus, multiple medications usage like diuretics, non-steroidal anti-inflammatory drugs (NSAIDs), tricyclic anti-depressants (TCAs), tea and toast diet with more water and less protein intake from many years and age-related decrease in glomerular filtration rate (GFR), all of which plays a crucial role in causing low sodium state chronically or even acutely [4,12]. On the contrary, our case report is unique as it specifically highlights the association of severe hyponatremia with indapamide to the level of 100 meq/l within two weeks of commencement in a middle-aged man without co-morbid illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Thiazide diuretics are commonly prescribed in controlling blood pressure and hyponatremia has been reported in patients receiving diuretics as a natural consequence of the therapy. Few case reports and studies have shown that thiazide or thiazide-like diuretics cause profound hyponatremia (110-125 mmol/l) and most of those cases were attributed to thiazide diuretic usage in females, elderly (≥65 years) and with multiple co-morbid conditions [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%